Voting against the separation of powers between legislature and administration - David Stadelmann; Reiner Eichenberger; Marco Portmann (Center for Research in Economics, Management and the Arts (CREMA), 2013)
We compare the votes of parliamentary representatives and their constituents on a popular initiative that directly aimed at weakening the separation of powers in 1922 in Switzerland. We analyze whether the strength of individual ties to the public service affect the probability of voting for the initiative , holding constituents' preferences constant. Our results indicate that while politicians tend to represent their constituents' preferences, representatives with ties to the public service have a higher probability of supporting the eligibility of public servants for the legislature. Thus, they favor reducing the separation of powers between legislature and administration.
Keywords: D72; D73; H83; 330; separation of powers; administration; public servants; legislative voting; constituents' preferences